COMPARISON OF NON-COLIFORM BACTERIA IN BALI CATTLE FAECES BASED ON LEVEL OF MATURITY AND MAINTENANCE PATTERN - Sulaksana, Kadek Andre; Suarjana, I Gusti Ketut; Besung, I Nengah Kerta (Buletin Veteriner Udayana; Vol. 9 No. 2 Agustus 2017, 2017)
This study aim was to determine the effect of maintenance type and maturity level of bali cattle to the total of non coliform bacteria in bali cattle. A total of 24 samples of bali cattle’s feces were used. This study was a Factorial 2 x 3 of group -randomised design, contained of two type maintenance (TPA Suwung and Sobangan) and three levels of cattle maturity (calves, heifers, and adult). The groups were based on time sampling. The data then analyzed using Analysis of Variance Test and continued by using Least Significant Different test. The results showed that the amount of non-coliform bacteria in adult bali cattle feces were higher then heifers and calves. Total of non coliform bacteria in bali cattle in  landfill was higher then the cattle that reared in captivity in Bali Cattle Breeding Center, the Sobangan village of Mengwi Badung regency.